Communication Strategies for Sustainable Forest Farmers’ Groups in the Special Region of Yogyakarta - Konselia D. Vera; Pudji Muljono; Dwi Retno Hapsari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study aims to formulate a communication strategy for sustainable forest farmer groups (FFG) in Jatimulyo Village, Special Region of Yogyakarta. The study employed a mixed-methods approach with an explanatory sequential design. Quantitative data were collected from 58 respondents who are members of the Wanapaksi FFG and analyzed using SEM-PLS based Importance Performance Map Analysis (IPMA), while qualitative data were gathered from 9 key informants to deepen the analysis results. The results indicate that the sustainability of the FFG is influenced by a participatory communication ecosystem. Based on the IPMA mapping, the indicators identified as top priorities for improvement (Quadrant IV) are the effectiveness of liberating pedagogy, participation (voice), and managerial capacity. All of which are highly important but currently underperforming. The communication strategy is framed within the “Wanapaksi Merekat: Listening to One Another, Managing Wisely, Growing Together Toward Sustainability” program, organised into five operational stages: research, planning, implementation, measurement, and reporting. This strategy focuses on creating safe spaces for dialogue, integrated governance training, and experiential learning to support the achievement of SDG 13 (Climate Action) and SDG 15 (Life on Land). Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality EducationSDG 13: Climate ActionSDG 15: Life on LandSDG 16: Peace, Justice and Strong InstitutionsSDG 17: Partnerships for the Goals